The Efficacy of Pelvic Floor Rehabilitation in the Treatment of Urinary Incontinence in Female Athletes: A Systematic Review - Andrea Demeco; Giulia Bartocci; Noemi Astore; Beatrice Vignali; Antonello Salerno; Stefano Palermi; Ruben Foresti; Chiara Martini; Cosimo Costantino (Sports)
Background and Objectives: Urinary incontinence (UI) prevalence reaches the 80% rate in female athletes involved in high-impact sports. In this context, although conservative treatment represents the first therapeutic choice, there is still a lack of knowledge on the efficacy of conservative programs in young female athletes. Therefore, the aim of this study was to investigate the role of pelvic floor rehabilitation in the treatment of UI in young nulliparous female athletes. We performed a literature search using PubMed, Medline, Cochrane Library, Web of Science, and Scopus. The selection of articles was conducted using a specific search string: “[((pelvic floor dysfunction) OR (urinary incontinence) OR (dyspareunia) OR (dysuria)) AND ((sport) OR (sports)) AND ((female) OR (woman) OR (women) OR (girl)) AND ((rehabilitation) OR (rehab) OR (pelvic rehabilitation) OR (exercise))]”. The review protocol was registered in PROSPERO with the ID CRD42024559990. A total of 1018 articles were found in all searches of the databases. After removing duplicates, 663 papers were reviewed in terms of title and abstract. Finally, a total of six studies were included in the present review. The results of this review show that conservative treatment with a personalised pelvic floor muscle training program (PFMTP) represents an effective treatment for UI, decreasing urine loss and improving maximum voluntary pelvic contraction; this is linked with an improvement in quality of life and sports performance, in particular when supervised by a physical therapist. Moreover, due to the reluctance of athletes to talk about UI, an educational program should be considered as part of a prevention programme in pre-season training.